Design, synthesis, and screening of ortho-amino thiophene carboxamide derivatives on hepatocellular carcinomaas VEGFR-2Inhibitors - Mohammed K. AbdElhameid; Madlen B. Labib; Ahmed T. Negmeldin; Muhammad Al-Shorbagy; Manal R. Mohammed (Taylor & Francis Group, 2018)
In this work, design, synthesis, and screening of thiophene carboxamides 4-13 and 16-23 as dual vascular endothelial growth factor receptors (VEGFRs) and mitotic inhibitors was reported. All compounds were screened against two gastrointestinal solid cancer cells, HepG-2 and HCT-116 cell lines. The most active cytotoxic derivatives 5 and 21 displayed 2.3- and 1.7-fold higher cytotoxicity than Sorafenib against HepG-2 cells. Cell cycle and apoptosis analyses for compounds 5 and 21 showed cells accumulation in the sub-G1 phase, and cell cycle arrest at G2/M phase. The apoptotic inducing activities of compounds 5 and 21were correlated to the elevation of p53, increase in Bax/Bcl-2 ratio, and increase in caspase-3/7.Compounds 5 and 21 showed potent inhibition againstVEGFR-2 (IC50 = 0.59 and 1.29 μM) and β-tubulin polymerization (73% and 86% inhibition at their IC50 values).Molecular docking was performed with VEGFR-2 and tubulin binding sites to explain the displayed inhibitory activities.